ANALISIS STRUKTUR MUSIKAL RAMPI RAMPO DI KECAMATAN MUARO BUNGO PROVINSI JAMBI - Anggi Dea Neta Utami; Esy Maestro; Jagar Lumban Toruan (FBS Universitas Negeri Padang, 2012)
Abstract The research was conducted with the aim to describe the results of analysis of the structure of a musical track in District Rantau Rampi Rampo Pandan Muara Bungo regency in Jambi Province. This research was content analysis (content analysis) approach descriptive method of analysis, the research found is rhythm (melodic and rhythmic) repetitive, harmony and melody minor chord progress (IV), kadens perfect, phrase antecedents, consistent and song form Rampi Rampo is a form1 (A-A1), tone motif m, n, o, p, a, b, c, b1, d, e, the expression in the form of songs and rhytme advices young couple.